Mobile Application Development with SMS and the SIM Toolkit - B.Guthery Scott (McGrraw-Hill, 2001)
Mobile Application Development Using SMS and the SIM Toolkit is just the guide you’ve been looking for if you’re building applications for GSM or 3G networks, wish you had sample code for reality-based applications, or want to add mobile extensions to your software products and corporate network. In this straight-talking tutorial, smart card expert Scott Guthery teams with information management specialist Mary Cronin to provide you with authoritative guidance on SIM application design, integration, and management for any platform. Seasoned developers will quickly learn how to: